SPATIAL ABILITY IN MEDICAL AND DENTAL EDUCATION: SCOPING REVIEW - Nabilla Riadi Nur Ramadhani; Dani Rizali Firman; Erli Sarilita; Yurika Ambar Lita (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2022)
Background: the ability to mentally manipulate 3D objects and understanding the relationships between structures is essential in many fields of medical and dental specialties. This scoping review of the literature on spatial ability in medical and dental education was conducted to provide a map of the literature and identify where gaps still exist for future research.Methods: the study was conducted using a scoping review method with guidelines from the Arksey and O'Malley framework to identify literatures related to the research topic. Searches was performed from February to May 2021 in PubMed, Cochrane, CINAHL and Google Scholar using keywords related to spatial ability, medical education and dental education. Literatures was also identified using snowballing technique. PRISMA-ScR analysis for study selection was performed.Results: fifteen articles were selected for review. Spatial ability correlates with performance in studying anatomical knowledge of medicine and dentistry, and surgery. 3D anatomical models are more effective when conveying complex spatial relationships than traditional 2D models. The Mental Rotation Test (MRT) is the most widely used test for measuring spatial abilities. The results of the measurement of spatial ability showed the superiority of males over females.Conclusion: spatial ability and learning in medical and dental education provide mutual benefits for both aspects. Additional spatial abilities module may be added to medical and dental education curricula to improve learning success